Applicability of bill of quantities in today's construction procurement - Razali, Atikah; Abdul Rashid, Khairuddin (2011)
Bill of quantities (B/Qs) is an essential document in a construction project which provides the detail of the contract amount. Historically, the formal form of B/Qs was initiated in the United Kingdom after the Industrial Revolution in the 19th century. They were mainly used by contractors for paying their workers and claiming payments from clients by submitting it as partisan final account. Particularly, B/Qs is widely used in the traditional procurement for cost estimating and as part of tender and contract document. However, as construction industry evolved and changed technologically, economically, legally, and procedurally, similarly goes to the usage of B/Qs in the construction projects. It is not known whether B/Qs in its current format suitable to be used with the more modern procurement systems or not. Based on literature, the issue on the declining usage of B/Qs due to the non-traditional procurement system adopted in construction industry has been encountered in the UK, Australia and also Malaysia construction industry due to several factors. One of the common factors is due to complex and time consuming on the preparation of B/Qs document. Thus, this research is intentionally to develop strategies to close the gaps between B/Qs documentation in terms of format and style with system of procurement. Besides that, this research may establish the functions of B/Qs in the construction procurement system.